Design and development of a reflective membrane for a novel Building Integrated Concentrating Photovoltaic (BICPV) ‘Smart Window’ system - Connelly, Karen; Wu, Yupeng; Chen, Jun; Lei, Yu (Elsevier, 2016)
As a new concept, Building Integrated Concentrating PV (BICPV) “smart window” system consisting of a thermotropic layer with integrated PVs is treated as an electricity-generating smart window or glazed façade. This system automatically responds to climatic conditions by varying the balance of solar energy reflected to the PV for electricity generation and transmitted through the system into the building for provision of light and heat. Its success heavily relies on the understanding of the relationship between the transmittance/reflectance properties and the composition of the thermotropic layer under different environmental temperatures. Herein, hydroxypropyl cellulose (HPC) polymer and gellan gum based hydrogel membranes with different compositions were synthesized as the reflective thermotropic layer for the smart BICPV system and their transmittance and reflectance were systematically investigated in terms of hydrogel composition and environmental temperature. Specifically, a switching temperature (Ts) of ~42 °C (6 wt. % HPC) was recorded, the measured transmittance decreases from ~ 90% to ~20%, with the temperature of the reflective layer increasing from 20°C to 60°C. No hysteresis in optical property was observed upon heating-cooling cycle of HPC membrane samples. The measured reflectivity increased with heating from ~10 % below the Ts to ~50 % above the Ts (for 6 wt. % HPC). These features indicate that the as-prepared HPC based thermotropic hydrogel layer holds great potential for application in next generation BICPV smart windows.